Peran Orang Tua dalam Menumbuhkan Minat Belajar Matematika pada Siswa Kelas Tinggi SDN Botodaleman Purworejo - Yuli Indah Sari; Mujiyem Sapti; Rintis Rizkia Pangestika (Perkumpulan Kualitama Edukatika Indonesia, 2021)
This study is a quantitative study using a survey method that aims to determine the influence of the role of parents in growing interest in learning Mathematics in high-class students at SDN Botodaleman Purworejo during the Covid-19 pandemic. The population and sample subjects in this study were all high school students at SDN Botodaleman Purworejo. The research instrument used was a questionnaire on the role of parents and students' interest in learning. The data analysis technique used is simple linear regression. The results of the hypothesis test obtained the value of Sig. (2-tailed) 0.000 < 0.05. Furthermore, the determination test R2 0.221 shows that the percentage of the contribution of the influence of the independent variable is 22.1%. This shows that 22.1% of students' interest in learning is influenced by the role of parents, while 77.9% is influenced by other factors. From these results it can be seen that the role of parents is influential in growing interest in learning Mathematics.